1973
DOI: 10.1002/art.1780160407
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Studies of Lymphoid Cells in the Rheumatoid Synovial Membrane

Abstract: The sublining layer of the rheumatoid synovium has been examined in the electron microscope. In this layer lymphocytes appeared to leave the blood by passing through the endothelial cytoplasm of venules and veins to form dense perivascular accumulations rich in either lymphocytes, plasma cells or both. Undifferentiated blast cells and plasmablasts were also observed in these collections. The finding of predominantly lymphocytic accumulations around some vessels and predominantly plasma-cellrich accumulations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2
1

Year Published

1974
1974
1998
1998

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(26 citation statements)
references
References 22 publications
2
21
2
1
Order By: Relevance
“…No lymphocytes were observed at sites close to the cartilage, but these cells were very conspicuous in the pannus tissue remote from the junction, as described by othcrs (30,31). Some studies have suggested that chondrocytcs participate in cartilage degradation, as judged by loss of pericellular proteoglycan and collagen (12,32).…”
Section: Discussionmentioning
confidence: 90%
“…No lymphocytes were observed at sites close to the cartilage, but these cells were very conspicuous in the pannus tissue remote from the junction, as described by othcrs (30,31). Some studies have suggested that chondrocytcs participate in cartilage degradation, as judged by loss of pericellular proteoglycan and collagen (12,32).…”
Section: Discussionmentioning
confidence: 90%
“…The DR+, 63D.3+ cells had an elongated appearance, with many vacuoles and lysosomes in their cytoplasm, and were a-naphthyl acetate esterase-positive. Thus, by histochemical, ultrastructural (29,30), and monoclonal antibody staining criteria (24,41), they appeared to be cells of the macrophage lineage. Similar conclusions have previously been reached on the basis of light microscopic examination of interstitial areas (35,37).…”
Section: Discussionmentioning
confidence: 93%
“…Clear cytoplasm contains numerous small vesicles and narrow tubules, whorl-shaped endoplasmic reticulum (arrowheads), and few lysosomes (original magnification x 3,300). areas have been described (23,30,31). We have examined the reactions of monoclonal antibodies with the cell membranes of the mononuclear cells in these areas and rn the lining and interstitial areas of the synovium, by use of an immunoelectron microscopic method.…”
Section: Discussionmentioning
confidence: 99%
“…The synovial membrane in rheumatoid arthritis (RA) is characterized by extensive infiltration of mononuclear cells (1,2). These cells are often present in histologically characteristic collections (3)(4)(5)(6), such as 1) lymphocyte-rich aggregates; 2) areas containing lymphocytes, plasma cells, and macrophages, which have been called transitional areas; and 3) plasma cell-rich areas (7).…”
Section: Interleukin-1 Lymphocyte Chemotactic Activity In Rheumatoid mentioning
confidence: 99%